Correlation between Uric Acid and Liptin with Its Ratio in a Sample of Iraqi Patients with Diabetes Mellitus - Ibraheam, Zeina Ismael (Al-Nahrain Journal of Science, 2018)
In this study the relation between uric acid and leptin hormone with its ratio, was investigated among sample of Iraqi diabetic patients. A case control study conducted in the National Diabetes Center, College of Medicine at Al-Mustansiryia University in Baghdad-Iraq. Hemoglobin A1c (HbA1c), fasting blood sugar, leptin and uric acid were measured. One hundred forty patients with DM was inhered in this study, and 100 subjects were healthy as a control revealed a highly significant increasing in serum (FBS), HbA1c, body mass index (BMI), Leptin and uric acid of diabetes patients than in healthy subjects(p < 0.0001). While the ratio of glucose /leptin of diabetes patients was highly significant decrease compare to healthy subjects. As well as the present study indicate a positive relation between serum uric acid with HbA1c of diabetes mellitus patients and uric acid with leptin diabetes mellitus patients ((p < 0.0001).